Development and Application of Solar-Powered Aircraft Technology - Xianglei Liu; Xinmeng Yang; Ruixiong Hu; Yimin Xuan (中国工程科学)
Solar-powered aircraft has the advantages of prolonged high-altitude flight, operational flexibility, and zero carbon emissions, making it one of the emerging fields that the global aerospace industry prioritizes. This study investigates the current development status of solar-powered aircraft in China and abroad and summarizes the development trends of its key technologies, including advanced aerodynamic design, efficient and low-cost solar cells, high-energy-density batteries, and efficient and wide-operating-condition propulsion. Based on the energy balance and mass balance principles, this study establishes an overall performance simulation model for solar-powered aircraft, predicting the development trends of its mass, sustainable flight altitude, and load capacity. The primary development direction of solar-powered aircraft is long-endurance, high-altitude, solar-powered unmanned air vehicles, which has important application prospects in the fields of military reconnaissance, environmental monitoring, and communication relay. Based on the predictive results and key technology research, this study proposes the short-, medium-, and long-term development goals and key tasks of solar-powered aircraft. Furthermore, it proposes strategies and policy recommendations to promote the sustainable development of solar-powered aircraft from three different levels: overall idea, technological breakthroughs, and system construction.